2019
DOI: 10.1016/j.jebo.2017.07.022
|View full text |Cite
|
Sign up to set email alerts
|

The economic functioning of online drugs markets

Abstract: The economic functioning of online drug markets using data scraped from online platforms is studied. Analysis of over 1.5 million online drugs sales shows online drugs markets tend to function without the significant moral hazard problems that, a priori, one might think would plague them. Only a small proportion of online drugs deals receive bad ratings from buyers, and online markets suffer less from problems of adulteration and low quality that are a common feature of street sales of illegal drugs. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 21 publications
(17 reference statements)
6
34
0
Order By: Relevance
“…Duxbury and Haynie (2018) analyze the network structure of opioid distribution through the Dark Web. They arrive to similar conclusions as Bhaskar et al (2019), finding that vendors' trustworthiness explains more variation in the overall network structure than the affordability of vendor products or the diversity of vendor product listings.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Duxbury and Haynie (2018) analyze the network structure of opioid distribution through the Dark Web. They arrive to similar conclusions as Bhaskar et al (2019), finding that vendors' trustworthiness explains more variation in the overall network structure than the affordability of vendor products or the diversity of vendor product listings.…”
Section: Introductionsupporting
confidence: 57%
“…In their analysis of more than thousand drug-selling vendors from about 40 countries, they conclude that drug sales accounted for about a quarter of the total revenue on the market, with ecstasy-type drugs dominating the wholesale activity. Bhaskar et al (2019) in their analysis of more than 1.5 million online drug sales focus on moral hazard, analyzing seller reputation and performance. They find that only a small proportion of on line drug deals received a bad rating from buyers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have considered the change in population [12]- [15], number of listings [12]- [15], [17], product prices [14], and volume of sales [14] often collected from scraped data [15] particularly scrapes collected by independent researcher Gwern Branwen [13], [14] though also through manual extraction [12]. For the most part, it has been concluded that the size of the ecosystem recovers after interventions [7], [10]- [14], [22].…”
Section: Related Workmentioning
confidence: 99%
“…However, when they focused the analysis on young people who admitted consuming, the results changed: the higher the unemployment rate, the easier young users perceived access to be. Unfortunately, the lack of data did not allow the authors to go further and study the consequences of the recent economic crisis for the informal economy or for the sale of drugs on the Dark Web (see Bhaskar et al, 2017).…”
Section: Conventional and Unconventional Pathways Of Youth Transitionsmentioning
confidence: 99%